2020
DOI: 10.29303/jbt.v20i3.2135
|View full text |Cite
|
Sign up to set email alerts
|

Study of dug well water quality in Labuan Bajo, Indonesia

Abstract: The dug well water quality in community settlements needs assessment to ensure its quality. The water has to meet the required physical, chemical, and bacteriological standards. This initial research aimed to determine the dug well water quality in Kampung Ujung, Komodo District, Labuan Bajo City, WestManggarai Regency in September 2019. The research method was used survey and laboratory. The two dug well was taken used a purposive sampling technique. The test parameters include temperature, turbidity, pH, sme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…It shows the pollution of shallow water in the Kampung Ujung area. This research concluded that the quality of the to dug wells in the Kampung Ujung Labuan Bajo area is not appropriate for use as rawmaterial for drinking water (Wolo et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…It shows the pollution of shallow water in the Kampung Ujung area. This research concluded that the quality of the to dug wells in the Kampung Ujung Labuan Bajo area is not appropriate for use as rawmaterial for drinking water (Wolo et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…To assess the people's perception of climate change and adaptation needs, a qualitative and quantitative questionnaire-based survey was carried out during the southwest monsoon season in India; the results revealed that the perceptions and the information gathered were the same as analyzed observed trends of climate data [50]. People's perception of climate variability (which includes heat, winter and summer temperature, reduced rainfall, and fewer floods) can be used to motivate people for some adaptations and mitigation measures, as an assessment of climate variability from the last 5 to 10 years in Bangladesh showed negative impacts in terms of agriculture, human lifestyle, and water resources of that region [24,[51][52][53][54][55][56]. Another questionnaire-based survey that observed climate change and people's perception of climate change was based on four variables: income, politics, agriculture, and economy in Montana.…”
Section: Climate Change Adaptation and Mitigation Strategiesmentioning
confidence: 99%
“…The results of another study showed that the quality of two dug well water samples in Kampung Ujung The Labuan Bajo area is no longer suitable for use as raw material for drinking water. Furthermore, the government must provide other water sources such as: addition of raw water storage tanks, so that the community does not depend completely in dug well water (Wolo et al, 2020). Sanitation and hygiene in water sources are significantly related to the presence of E. coli in household drinking water (Ondieki et al, 2022).…”
Section: Samplementioning
confidence: 99%
“…Research in Kermansyah showed that Fecal coliform was found in water sources in urban (22%) and rural (45%) (Davoodi et al, 2018) . Preliminary research on dug well water in Labuan Bajo showed that the E. coli parameters exceeded the requirements (Wolo et al, 2020) . A water inspection study using the MPN (Most Probable Number) method which consists of 3 tests, namely, a presumption test, a confirmatory test, and a reinforcing test showed that from 15 drinking water samples 8 samples of drinking water were tested positive for Coliform bacteria contamination, while 7 other samples were negative.…”
Section: Introductionmentioning
confidence: 99%